Phylogenetic position of Tarsius bancanus based on partial Cytochrome b DNA Sequences - Badrul Munir, Md Zain; S.J., Lee; Maklarin, Lakim; Ampeng, A.; Mahani, M.C. (Journal of Biological Sciences, 2012)
This study was carried out to ascertain the molecular phylogenetic position of Tarsius bancanus among Malaysian primates based on the partial of Cytochrome b (cyt b) gene sequences. A total of five samples of Tarsius bancanus from Sabah, Malaysia, were used in this study. Several other Malaysian primates were also included in the analysis (Leaf monkeys (Presbytis and Trachypithecus), Macaques (Macaca), Siamang (Symphalangus) and Slow loris (Nycticebus). We also included DNA sequences of several prosimians (Galago, Cheirogaleus, Daubentonia, Indri, Avahi, Lemur and Lepilemur) from GenBank. In addition, one individual of orang utan (Pongo pygmaeus) and human (Homo sapiens) were used as outgroups to root the tree. All taxa were analysed using character method (Maximum Parsimony, MP) and distance method (Neighbor-Joining, NJ). From the 375 examined characters, 43.2% were constant characters while 4.8% characters were parsimony uninformative whereas 52.0% characters were parsimony informative. Tree topologies discriminated three major clades in which primitive primates, Old World Monkeys and Anthropoids belongs to their own monophyletic clades. Both MP and NJ trees showed that T. bancanus was placed in primitive primates group.